2022
DOI: 10.1007/s40670-021-01435-3
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Effective Online Anatomical Sciences Teaching and Assessments in the Pandemic Era of COVID-19 Should be Evidence-Based

Abstract: The world has changed rapidly since the emergence of the COVID-19 pandemic, and the education community has not been immune to these changes. With abrupt school closings and a rapid transition to online teaching and learning, the educational technologies have been stretched to their limits and pedagogic approaches blossomed. As the world strives to reestablish normalcy, it will be under the influence of the long-lasting impact of the pandemic. This manuscript provides recommendations for the online conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Results of this study will advance the development of evidence‐informed approaches to promote anatomical education and authentic learning in the future, pertinent to effective anatomical teaching in the pandemic era of COVID‐19 (Mishall et al, 2022; Shin et al, 2022). Future studies that explore this educational model in medical, dental and allied health anatomy regarding students' engagement and performance as well as academic perceptions are needed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Results of this study will advance the development of evidence‐informed approaches to promote anatomical education and authentic learning in the future, pertinent to effective anatomical teaching in the pandemic era of COVID‐19 (Mishall et al, 2022; Shin et al, 2022). Future studies that explore this educational model in medical, dental and allied health anatomy regarding students' engagement and performance as well as academic perceptions are needed.…”
Section: Discussionmentioning
confidence: 92%
“…Results of this study will advance the development of evidenceinformed approaches to promote anatomical education and authentic learning in the future, pertinent to effective anatomical teaching in the pandemic era of COVID-19 (Mishall et al, 2022;Shin et al, 2022). Future studies that explore this educational model in medical, dental and allied health anatomy regarding students' en- In addition, the recent university-wide course review at Swinburne University of Technology has included a review of teaching in the anatomy curricula across all health sciences and allied health disciplines, and there is a willingness to introduce a greater proportion of digital learning strategies and more experiential learning activities.…”
Section: Future Perspectivesmentioning
confidence: 90%
“…Therefore, the development of digital competencies and the use of education has yet to become future-ready and requires various stakeholders' e.g., involvement in improving the hybrid learning approach so that it is responsive and adaptable to future uncertainties Xiau & Adnan, 2022). Continuous needs assessments and the reevaluation of the anatomy curricula are also needed to establish a basis for curricular changes and redevelopment (Mishall et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the utility of summative anatomy assessments has declined during the Covid‐19 pandemic as anatomy educators have struggled to ensure the validity, reliability, practicality, feasibility, cost‐effectiveness, and educational impacts of online assessments (Van Der Vleuten, 1996). Accordingly, formative assessments must be leveraged alongside the best practical assessment methods in medical education (i.e., the utility of assessment and constructive alignment) in order to ensure high‐quality anatomy assessment during the pandemic (Mishall et al, 2022). These assessment practices must be continuously re‐examined and re‐evaluated by anatomy educators to suit anatomy education's current and future needs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were discordant with some studies (Nepal et al, 2020;Bączek et al, 2021;Totlis et al, 2021;Wilhelm et al, 2022). However, similar studies and expert opinions have suggested that online learning of anatomy could be as equally effective as face-to-face learning (Zhou et al, 2020;McKivigan et al, 2021;Zheng et al, 2021;Mishall et al, 2022). This suggests that the strong theoretical grounding accumulated through distance teaching during the pandemic-induced lockdown era was beneficial for scheduled dissection work after returning to school.…”
Section: F I G U R Ementioning
confidence: 97%